Trend of fall-related mortality among the elderly - Yara Cristina Martins Monteiro; Maria Aparecida da Silva Vieira; Priscila Valverde de Oliveira Vitorino; Silvio José de Queiroz; Gabriela Moreira Policena; Adenicia Custódia Silva e Souza (SciELO, 2021)
ABSTRACT Objective: To analyze the temporal trend of fall-related mortality in elderly in Brazil from 2008 to 2016. Method: Study of time series of rates of fall-related mortality according to CID-10 from 2008 to 2016. Data from the Mortality Information System on death registers of people ≥ 60 living in Brazil were used. The specific rates of fall-related mortality among the elderly were calculated through the ratio between the number of deaths and the elderly population of that year and region. The populational information was obtained from the 2000 and 2010 censuses. The variation rate and temporal trend were obtained through linear regression (p < 0.05). Results: The fall-related deaths among the elderly aged ≥ 60 amounted to 72,234 (31.2%). Falls from the same level were the most frequent (53.8%) and death rates in all ages ranged from 29.7 to 44.7 per 100,000 elders. Fall-related deaths increased with age. Conclusion: There was a growing trend of fall-related deaths among elderly in all age groups, an event which is avoidable through the adoption of preventive measures. The high rates and growing trend of fall-related deaths, as well as the aging of the Brazilian population, suggest that public policies for protecting the elderly must be prioritized.